Peran Konselor Sebaya dalam Menangani Anak Korban Kekerasan Seksual di Sekolah - Muhammad Abi Januar; Muhamad Sofiyudin; Kevin Ibrahim Hasan; Ati Kusmawati (Concept: Journal of Social Humanities and Education, 2024)
This article aims to explain and describe the role of peer counselors in dealing with child victims of sexual violence, especially in schools. The discussion of this article was obtained through a literature study from various reading sources such as journals and books used to describe theories related to child development, explore the impact of sexual violence on victims, and describe the role of social workers in dealing with the problem of sexual violence in children. The high rate of sexual violence against children shows the importance of handling child victims of sexual violence. In this case, peer counselors can provide support and motivation to children who are victims of sexual violence. In addition, counselors can be friends to tell stories from children who are victims of this violence. In this case, Peer Counselors can also conduct Counseling. Counseling is carried out by intervening negative thoughts of children that arise due to sexual violence in various ways, such as stopping negative thoughts. In addition, cognitive therapy can also be done by changing or exchanging thoughts, for example counselors help children to memorize short verses in the form of statements that are contrary to the concerns experienced by children. The child then repeats the verse to get rid of his worries.